Decompose Dual Nationality (Dual Citizenship) In Indonesia In Human Rights Perspective and Welfare State - Supriyadi A Arief (Faculty of Law, Universitas Pattimura, 2020)
The state is obliged to fulfill and protect the rights of its citizens, including the right to citizenship status. This status will facilitate citizens in living their lives, both in the country that grants citizenship status and in other countries. The high mobility of citizens results in boundaries between countries no longer limited by distance and time. As a result, a person's citizenship status can change, either because of personal needs or obligations of the second country which requires citizens to have citizenship status of the country. The problem in this research is to what extent dual citizenship in the perspective of human rights can realize a welfare system ?. This research is a normative study using a statutory approach, historical approach, and case approach. The results of the study indicate that the guarantee of the right to citizenship status is an inseparable part of the concept of human rights as contained in the 1945 Constitution of the Republic of Indonesia. However, with the rapid flow of global developments causing dual citizenship accommodation in Indonesian citizenship law is something that can be applied in the future. Recognition of dual citizenship can be seen as part of the efforts of the state to bring prosperity to all citizens and protect the citizens' rights to citizenship status.